MASCULINISM IN NOVEL FIFTY SHADES OF GREY: A CULTURAL STUDY - Danar Cristanto (English Teaching Journal : A Journal of English Literature, Language and Education, 2015)
In the modern age, there are many media to serve entertainment. One of the media is novel. Novel is the object material for this research study. This research analyzes about masculinism in Novel Fifty Shades of Grey. It analyzes focus in masculinism that happen in American Culture related Novel Fifty Shades of Grey. The aim of this research is to analyze the existence of masculinism in American Culture. A Cultural Study is chosen by the researcher in order to analyze the research problems. The research method applied is descriptive qualitative research and popular literature theory. The source of the data are taken from Novel Fifty Shades of Grey, books, articles, webs, and journals that related with the analysis of the masculinism in American Culture as study of culture. The technique of collecting data is by using document technique. The techniques of analyzing data are content or document analysis.Fifty Shades of Grey is a romance novel that contains complicated relationship between main characters. The plot of masculinism novel always makes a man has more power toward woman. The popularity of masculinism novel is influenced by masculinism practice in the Culture. Masculinism in modern age still exists in society in difference ways that masculinism is exist in American Culture by the peoples think, make and do. The purposes of the masculinism practices are not only to show care, interest and loves but alsoforce man’s desire and isolate their woman from public. This research uses theory of masculinism which masculinism is a system of interrelated social structures which allow men to exploit women. The result of the research is masculinism still exist in American Culture.